USING CEMENT KILN DUST AS LOW PERMEABLE BARRIER FOR RESTRICTION THE PROPAGATION OF CADMIUM IONS TOWARDS THE WATER RESOURCES - & Faisal, Ibreesam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to determine the interaction of cement kiln dust - aqueous solution contaminated with Cadmium ions was studied through set of batch tests with operational conditions of contact time ≤120 min, sorbent dosage from 0.05 to 1 g/100 mL and agitation speed ranged from 50 to 300 rpm for initial concentration of 50 mg/L with initial pH of 3 to simulate the acetogenic phase in the sanitary landfill. The best values of these conditions are 1 hr, 0.7 g/100 mL and 250 rpm respectively, To obtain maximum removal efficiencies of 97.6%. Freundlich and Langmuir models have a high ability in the representation of the sorption data with determination coefficient (R2) greater than 0.97 and the sorption capacity reached to 84.1 mg/g. This certifies that the physical sorption and chemisorption can occur together to remove Cadmium ions from the aqueous solutions. Tests elucidated that the average coefficient of the hydraulic conductivity is equal to 9.7×10-13 m/s and this is suitable for LPB. Finally, COMSOL Multiphysics 3.5a package was able to simulate the distribution of cadmium ions concentrations within two-dimensional physical model packed with sand aquifer and CKD LPB. A good matching between model predictions and experimental results are recognized at selected points up and down gradient of LPB.